2022
DOI: 10.3390/insects13060524
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Non-Consumptive Predation Risk of Coccinella septempunctata (Coleoptera: Coccinellidae) on the Population Growth of Sitobion miscanthi (Hemiptera: Aphididae)

Abstract: How the non-consumptive effects (NCEs) of predators influence the development, survival, fecundity, and population growth of prey has not been well documented, which is the primary consideration for the compatibility of prey with its natural enemies in agricultural ecosystems. We herein employed the age-stage, two-sex life table to examine the NCEs of the predator Coccinella septempunctata on the life-history traits and population growth of prey Sitobion miscanthi via caged predator (prey co-existing with cage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Historically, the traditional life table did not consider stage differentiation, however Chi (1988) expanded the theory of age-stage, two-sex life table to consider both male and female individuals and changeable development rates between them. This method was used in many studies based on predators and parasitoids (Farhadi et Wang et al 2022). In this study, the age-stage, two-sex life table approach was used to assess the effect of photoperiod on population parameters of P. persimilis fed on T. urticae.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the traditional life table did not consider stage differentiation, however Chi (1988) expanded the theory of age-stage, two-sex life table to consider both male and female individuals and changeable development rates between them. This method was used in many studies based on predators and parasitoids (Farhadi et Wang et al 2022). In this study, the age-stage, two-sex life table approach was used to assess the effect of photoperiod on population parameters of P. persimilis fed on T. urticae.…”
Section: Introductionmentioning
confidence: 99%
“…Chi and Yang (2003) examined the age‐stage, two‐sex life table for the ladybird predator, Propylaea japonica (Col.: Coccinellidae), and indicated that it could accurately describe the variability of predation rate with age and stage. This method was used in many studies based on predators and parasitoids (Ding et al, 2020; Farhadi et al, 2011; Ou et al, 2021; Ramos Aguila et al, 2021; Wang et al, 2022). Chi and Yang (2003) noted that in order to accurately reflect the variability of predation rate with stage and age, the daily consumption rates across the lifelong of a predator population should be assessed by the age‐stage structure of the life table.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous natural enemies of insect pests in nature, such as parasitic wasps ( Daniel et al., 2023 ), ladybirds, and lacewings ( Wang et al., 2022 ; González-Ruiz et al., 2023 ). Additionally, arthropods like spiders and mites are capable of preying on a diverse range of pests ( Vervaet et al., 2022 ; Fidelis et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%